2023
DOI: 10.1093/joc/jqad002
|View full text |Cite
|
Sign up to set email alerts
|

Inequities of race, place, and gender among the communication citation elite, 2000–2019

Abstract: A recent wave of studies has focused on the identities of communication scholars, quantifying the degree to which Whites, men, and Americans dominate the discipline.This study analyzes the communication citation elite (CCE)—a group of 1,675 highly cited scholars in communication research—in terms of race, gender, and country of employment over 20 years. Applying computational methods and content analysis, we find that 91.5% of first-author CCE members are White, 74.3% are men, and 78.6% work in the United Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 49 publications
0
3
0
3
Order By: Relevance
“…Such trends align with recent studies analyzing inequities of race, place, and gender. Freelon et al (2023) analyzed the communication citation elite (CCE)-a group of 1,675 highly cited scholars in communication research-by race, gender, and country of employment more than 20 years. They found that 91.5% of first-author CCE members are White, 74.3% are men, and 78.6% work in the United States (Freelon et al, 2023).…”
Section: Americans White People and Men Dominate The Deutschmann Awar...mentioning
confidence: 99%
See 1 more Smart Citation
“…Such trends align with recent studies analyzing inequities of race, place, and gender. Freelon et al (2023) analyzed the communication citation elite (CCE)-a group of 1,675 highly cited scholars in communication research-by race, gender, and country of employment more than 20 years. They found that 91.5% of first-author CCE members are White, 74.3% are men, and 78.6% work in the United States (Freelon et al, 2023).…”
Section: Americans White People and Men Dominate The Deutschmann Awar...mentioning
confidence: 99%
“…Freelon et al (2023) analyzed the communication citation elite (CCE)-a group of 1,675 highly cited scholars in communication research-by race, gender, and country of employment more than 20 years. They found that 91.5% of first-author CCE members are White, 74.3% are men, and 78.6% work in the United States (Freelon et al, 2023). The dominance of White men resulted from the dominance of the scholarly field by White men, which, in turn, reflect the social norms of the time.…”
Section: Americans White People and Men Dominate The Deutschmann Awar...mentioning
confidence: 99%
“…Por décadas, el campo de la comunicación ha sido cuestionado por mantener procesos de exclusión que han limitado su riqueza y pluralidad. Una amplia investigación sistemática confirma que estos procesos de exclusión se verifican en temas tales como la discriminación racial (Chakravartty et al, 2018;Freelon et al, 2023), de género (Wang et al, 2021;Knobloch-Westerwick & Glynn, 2013), de patrones de citación (Demeter, 2018;Salvador-Mata et al, 2023), de abordajes metodológicos (Walter et al, 2018), epistemológicos (Bryant & Miron, 2004), geográficos (Albuquerque, 2020) e inclusive lingüísticos (Waisbord, 2016). De manera particular, la variada y rica discusión del campo que ha tenido lugar en América Latina ha sido parte de este proceso de exclusión y marginalización.…”
Section: Introductionunclassified
“…Cada vez más se observan esfuerzos por denunciar estos procesos de exclusión y marginalización (Freelon et al, 2023;Salvador-Mata et al, 2023), y también de visibilizar las voces excluidas y poner en la agenda académica esas "otras narrativas" que han ofrecido caminos renovados para reflexionar sobre el campo (Simonson et al, 2022). En este sentido, cabe destacar la publicación de Oliveira Paulino et al (2020), que pone en conversación a investigadores latinoamericanos adscritos a AlAIc con sus homólogos europeos de ecreA (European Communication Research Association), para juntos propiciar una reflexión más holística del campo de la comunicación.…”
Section: Introductionunclassified
“…Crucially, scholarship on racialized groups, their use of digital media, and its impact on online communities heightens efforts to validate individuals that are historically left out of academic discussion (Freelon et al, 2023). Black Americans are uniquely situated in a position that faces systematic barriers against them, as they are overrepresented in the prison population, homeless population, and children in the foster care system.…”
mentioning
confidence: 99%